If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -3m = 7 Solving 13 + -3m = 7 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + -3m = 7 + -13 Combine like terms: 13 + -13 = 0 0 + -3m = 7 + -13 -3m = 7 + -13 Combine like terms: 7 + -13 = -6 -3m = -6 Divide each side by '-3'. m = 2 Simplifying m = 2
| 10x=-4(2x-9) | | 35+5x-11=-6(2-x)+8 | | 16x^2+10x-27=-6x+5 | | -x=-6y+19 | | 10-(x+2)=-28-5 | | 23+x=-21 | | 10x-5=-75 | | 1-8(x-2)=2x+17 | | Y-8=-2x | | 3x-9=4x+12+6 | | 24x+12y=0 | | 2x=36-10x | | 6x+7+4+2x+5=8 | | e^2x+1=12 | | 5x-7=-30 | | -8-3x-x=2 | | 2x=1.5x-3 | | 4x-3/8y-6 | | 16=7+3v | | 21=-3x-2x-9 | | 2x=1.5-3 | | 12-3G=9 | | 115-5p=45 | | (3-5i)-2(6+3i)= | | c=24x+12y | | 288=6(6x+6) | | 1200(9.8)(sin(30))= | | 5n+6-5n=-12-6n | | 7sinx+11=5 | | 2=14-2p | | 1+3n=9+4n | | x^5-10x^3+25x=0 |